Sistem Informasi Perizinan PAUD Dinas Pendidikan OKU Selatan Dengan Metode Extreme Programming - Putra, Alfinda Retno; Ulfa, Maria; Sopiah, Nyimas; Ariandi, Muhamad (STMIK Banjarbaru, 2023)
Currently the OKU Selatan Education Office is still carrying out conventional data collection so that data processing is still ineffective and still uses a manual system in terms of school administration management, resulting in the issuance of paper, limited available data, and a lack of PAUD data integrity. The main objective of this study is to build an information system that focuses on fulfilling early childhood education at the South OKU Education Office. Through the application of the Extreme Programming method, this study aims to improve service quality and administrative efficiency. It is hoped that this information system will simplify the data collection process, allow access to information from various parties, and as a whole can improve the quality of education in PAUD. The results of this study make a significant contribution in overcoming obstacles in data management and PAUD licensing. This information system is capable of having a positive impact on administrative efficiency and improving educational services in the region.Keywords: Keywords: Information Systems; Licensing; Institutional; Early childhood education programs; Extreme Programming AbstrakSaat ini Dinas Pendidikan OKU Selatan masih melakukan pendataan secara convesional sehingga dalam pengolahan data masih kurang efektif dan masih mengunakan sistem manual dalam hal tata kelola Administrasi Sekolah sehingga mengakibatkan penumpukan kertas, keterbatasan data yang tersedia, dan kurangnya integritas data PAUD. Tujuan utama dari penelitian ini adalah membangun sebuah sistem informasi yang fokus pada perizinan PAUD di Dinas Pendidikan OKU Selatan. Melalui penerapan metode Extreme Programming, penelitian ini bertujuan untuk meningkatkan mutu pelayanan dan efisiensi administrasi. Diharapkan bahwa sistem informasi ini akan mempermudah proses pendataan, memungkinkan akses informasi dari berbagai pihak, dan secara keseluruhan, meningkatkan kualitas pendidikan di PAUD. Hasil penelitian ini memberikan kontribusi yang signifikan dalam mengatasi kendala-kendala dalam pengelolaan data dan perizinan PAUD. Sistem informasi ini mampu memberikan dampak positif dalam efisiensi administrasi dan peningkatan pelayanan pendidikan di wilayah tersebut.